Next Generation Citizen Science Using Anecdata.org - Disney, Jane; Bailey, Duncan; Farrell, Anna; Taylor, Ashley (Maine Policy Review, 2017)
Crowdsourcing scientific data, also known as citizen science, is a new and rapidly growing field. The MDI Biological Laboratory in Bar Harbor, Maine, has developed Anecdata.org, an innovative online platform for citizen science projects to collect, manage, and share environmental data. Anecdata currently hosts 48 projects from organizations around the United States and abroad, with new projects emerging every year. Anecdata provides features that help both project managers and participants collect actionable data and interpret what the data mean, so that effective environmental improvements can be achieved. These features include self-designed datasheets, photo uploading and archiving, and data visualization through graphing and mapping. New features are being developed to meet emerging project needs, including video upload, predictive modeling, and community-building communications tools.
Keywords: Maine; citizen science; online platforms; data management